CGIAR Report Concerning Centers’ Implementation of their Article 15 Agreements: A submission to the Tenth Session of the Governing Body of the International Treaty on Plant Genetic Resources for Food and Agriculture - CGIAR (2023)
This report provides an update on the status, as of December 31, 2022, of the plant genetic resources for food and agriculture (PGRFA) collections maintained by the eleven CGIAR Centers that signed Article 15 agreements with the Governing Body of the International Treaty on Plant Genetic Resources for Food and Agriculture (Plant Treaty) in 2006.